Analisis Model Komunikasi dalam Kampanye Lingkungan Hidup Greta Thunberg di Instagram - Samanda, Glen Aviaro (Universitas 17 Agustus 1945 Surabaya, 2025)
This study examines the communication model in Greta Thunberg’s environmental campaign on Instagram using Aristotle’s rhetorical approach: ethos, pathos, and logos. The research explores how Greta builds credibility as an activist (ethos), engages audience emotions to raise awareness (pathos), and strengthens her arguments with scientific data (logos). A library research content analysis of selected posts from @Gretathunberg identifies communication patterns in her digital campaign. Findings indicate that Greta effectively utilizes Instagram as a persuasive communication tool. Ethos is built through her global recognition as a young activist. Pathos is evident in emotional language, strong metaphors, and urgent calls to action, while logos is reinforced through scientific evidence and expert references. Instagram’s visual and interactive features enhance message dissemination, enabling audiences to actively engage, share content, and participate in discussions rather than being passive recipients. This study concludes that Aristotle’s rhetorical theory remains highly relevant in digital communication. Through a strategic combination of ethos, pathos, and logos, Greta Thunberg successfully mobilizes a global movement, raising public awareness and driving participation in climate action. Keywords: Rhetoric, Instagram, Campaign, Social Media, Activism